Early exposure to Aroclor 1254 in vivo disrupts the functional synaptic development of newborn hippocampal granule cells. (2nd November 2016) - Parent, A. S.; Pinson, A.; Woods, N.; Chatzi, C.; Vaaga, C. E.; Bensen, A.; Gérard, A.; Thome, J. P.; Bourguignon, J. P.; Westbrook, G. L.
Abstract: Neurogenesis in the dentate gyrus is sensitive to endogenous and exogenous factors that influence hippocampal function. Ongoing neurogenesis and the integration of these new neurons throughout life thus may provide a sensitive indicator of environmental stress. We examined the effects of Aroclor 1254 (A1254), a mixture of polychlorinated biphenyls (PCBs), on the development and function of newly generated dentate granule cells. Early exposure to A1254 has been associated with learning impairment in children, suggesting potential impact on the development of hippocampus and/or cortical circuits. Oral A1254 (from the 6th day of gestation to postnatal day 21) produced the expected increase in PCB levels in brain at postnatal day 21, which persisted at lower levels into adulthood. A1254 did not affect the proliferation or survival of newborn neurons in immature animals nor did it cause overt changes in neuronal morphology. However, A1254 occluded the normal developmental increase in sEPSC frequency in the third post‐mitotic week without altering the average sEPSC amplitude. Our results suggest that early exposure to PCBs can disrupt excitatory synaptic function during a period of active synaptogenesis, and thus could contribute to the cognitive effects noted in children exposed to PCBs. Abstract : Environmental exposure PCBs has been associated with cognitive deficits in children. We assessed the effects of early exposure to PCBs on newly generated neurons in the mouse hippocampus as a sensitive indicator of neural dysfunction. Although the proliferation and survival of newborn neurons was not affected, PCBs interfered with functional synaptic development that could contribute to their neurotoxicity.